Review of the species of Ittys (Chalcidoidea: Trichogrammatidae) occuring in the United States, with the description of four new species - George, Jeremiah N. (Zootaxa, 2007)
The United States fauna of the genus Ittys (Trichogrammatidae: Paracentrobiini) is revised for the first time. This revision includes a redescription of the genus, redescriptions of the named North American species with illustrations of diagnostic characters. The genus Ittys contains three described North American species which are all considered synonyms of the widespread Ittys ceresarum (Ashmead). Four new species from the United States I. californica n. sp., I. infuscata n. sp., I. macfarlandi n. sp. and I. inermis n. sp. are described as new.